Health-related Quality of Life and Mental Health of Elderly by Occupational Status - Yeunhee KWAK; Yoonjung KIM (Tehran University of Medical Sciences, 2017)
Background: This study aimed to identify the association between health-related quality of life and mental health by elderly Koreans' occupational status. Methods: This descriptive cross-sectional study consisted of a secondary analysis of data from the Korea National Health and Nutrition Examination Survey V-3 (2012). The sample comprised 1431 people aged 65 yr and older. Results: Compared to participants employed, those not showed lower HRQOL. Occupational status significantly affected all of the EuroQoL-5 Dimensions (EQ-5D): mobility, self-care, usual activity, pain/discomfort, and anxiety/depression. Unemployed participants had more suicidal ideation. Among employed elderly persons, significant differences were found between manual and non-manual workers in the EQ-5D index and EQ-5D for mobility and pain/discomfort. Manual workers experienced more depression and suicidal ideation than did non-manual workers. Conclusion: The occupational status of elderly individuals accounts for differences in their quality of life and mental health status. Therefore, additional jobs should be created for the elderly in order to improve their quality of life and mental health.